2022
DOI: 10.1007/s11356-021-17851-2
|View full text |Cite
|
Sign up to set email alerts
|

An extended hybrid fuzzy multi-criteria decision model for sustainable and resilient supplier selection

Abstract: The formalization and solution of supplier selection problems (SSPs) based on sustainable (economic, environmental, and social) indicators have become a fundamental tool to perform a strategic analysis of the whole supply chain process and maximize the competitive advantage of firms. Over the last decade, sustainability issues have been often considered in combination with resilient indexes leading to the study of sustainable-resilient supplier selection problems (SRSSPs). The current research on sustainable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 107 publications
(130 reference statements)
0
31
0
Order By: Relevance
“…Refs. [11,15,18,[51][52][53][54] adopted conventional BMW approaches to determine the appropriate SSS. Refs.…”
Section: Distribution Of Papers Concerning Applied Methodsmentioning
confidence: 99%
“…Refs. [11,15,18,[51][52][53][54] adopted conventional BMW approaches to determine the appropriate SSS. Refs.…”
Section: Distribution Of Papers Concerning Applied Methodsmentioning
confidence: 99%
“…After determining the criteria weights, the problem comes to selecting the optimal solution from alternatives. Various MCDM techniques are used to deal with SS, such as VIKOR (Kumar and Barman 2021;Wu et al 2019a), TOPSIS (Afrasiabi et al 2022;Ambrin et al 2021), ANP (Khan et al 2018), and so on. Yu et al (2019) used TOPSIS technique to rank the alternatives from the perspective of sustainability.…”
Section: Mcdm Methods About Supplier Selectionmentioning
confidence: 99%
“…They considered the uncertainties parameters in the model subjections and solved their model based on a real case study. Afrasiabi et al ( 2022 ) suggested a hybrid model based on MCDM techniques for sustainable and resilient supplier selection. They tried to consider the uncertainties and disruptions may occur during COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%